Removal of levofloxacin from aqueous solutions by using micro algae: optimization, isotherm, and kinetic study - Khitam Salim Shakhir; Fadia A. Sulaiman; Abeer I. Alwared; Noor A. Mohammed (Results in Engineering, 2024)
This study was focused on the response surface methodology modeling of the removal of levofloxacin residue using microalgae as adsorbent. The microalgae categories Cladophora was characterized by Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) analysis techniques. The efficacy of LEV removal was evaluated by the historical data of different variables (time, pH, algal dosage, and LEV concentration) using Central Composed Design (CCD). The predicted results of the model demonstrated that the expected responses are reasonably close to the actual data, demonstrating the efficiency of this method in producing an accurate prediction. The model was found to be significant based on its coefficient of determination, which was 0.914, along with the fitted and projected values of 0.9029 and 0.8967. Furthermore, the results of the predicted reaction optimization showed that the maximum LEV elimination could be achieved within a time of 90 min, a pH of 6 and 0.2 g/L of micro algae. The model was validated experimentally with 95.45 % of LEV elimination efficiency. In addition, it is observed that the LEV removal process followed Langmuir model and pseudo-second order kinetic in majority of the cases with R2 of 0.9959. As a result of the dead algae's simple use and high adsorption effectiveness, the results demonstrated the possible use of antibiotics in aqueous solutions.